AB1142 PROGNOSTIC VALUE OF 18F-FLUORODEOXYGLUCOSE PET-CT SCORE AT BASELINE ON THE THERAPEUTIC RESPONSE TO PREDNISONE IN PATIENTS WITH POLYMYALGIA RHEUMATICA. (June 2019) - Giraud, Nicolas; Sondag, Maxime; Charpentier, Aline; Boulahdour, Hatem; Prati, Clément; Wendling, Daniel; Verhoeven, Frank
Abstract : Background: Polymyalgia rheumatica (PMR) is one of the most common inflammatory rheumatic diseases. To date, there is no imaging procedure that can be used as a prognostic factor for good or poor response to corticosteroid therapy Objectives: To evaluate the prognostic value of 18F-fluorodeoxyglucose PET-CT (FDG-PET/CT) score at baseline, on the therapeutic response to prednisone, in patients with polymyalgia rheumatica (PMR). Methods: This is a monocentric retrospective study realized at the university hospital of Besancon. We included patients with a diagnosis of PMR meeting the 2012 ACR/EULAR criteria, who had performed a FDG-PET/CT at baseline, between december 2012 and december 2017. Patients were treated with an initial prednisone dose of 0.3mg/kg a day, progressively decreased following a standardized tapering dose protocol (10%/month). We excluded patients who received corticosteroids before the FDG-PET/CT, or without baseline FDG-PET/CT. Seventeen specifics previously described hotspots were visually analyzed (1). We realized a semi-quantitative analysis of FDG uptake (4-point score from 0 to 3), following Goerres scoring system (2). Hotspot with 0 indicating no uptake (same as bone); 1, slight uptake; 2, moderate uptake (same as liver); and 3, uptake higher than the liver, with a global range score of 0 to 51. Then we defined two groups of patients according to their resistance to prednisone at 12 months, defined as the reoccurrence of symptoms and/or an increase of systemic inflammation twice during the prednisone tapering. Results: 33 patients where included: 14 (42%) in the group "resistant "and 19 (58%) in the group "sensitive". There were 57.6% of women, with a mean age of 67.57 ± 11, 63 years. The mean CRP at baseline was 45.02 ± 39.59 mg/L. The mean FDG-PET/CT score at baseline was 18/51. The FDG-PET/CT score at baseline was significantly lower in the resistant group (13.1 vs 22.8/51, p =0.019). Resistant patients were younger (61.1 vs 72.4 years, p <0.01), and mostly men (66.5% vs 22%, p<0.02). ROC curve showed a threshold of 9.5/51 with a sensitivity of 61.54% and a specificity of 84.21% [AUC 0.76 (+/- 0.089), p= 0.014]. There was no statistically significant difference concerning CRP at baseline (48.6mg/l vs 44.8mg/l; p= 0.58), and no correlation between CRP and PET/CT score (r =0.25, p=0.15). The prevalence of synovitis (21% vs 37%, p=0.46), and neoplasia (0% vs 15.79%, p=0.79) were similar between the two groups. Conclusion: Our results suggest that in patients with PMR, a baseline FGD-PET/CT score over 9.5/51 score is predictive of a good response to prednisone. References: [1] Sondag.M, et al. Utility of 18F-fluoro-dexoxyglucose positron emission tomography for the diagnosis of polymyalgia rheumatica: a controlled stud. Rheumatology 2016 Aug;55(8):1452-7. [2] Goerres GW, Forster A, Uebelhart D, et al. F-18 FDG whole-body PET for the assessment of disease activity in patients with rheumatoid arthritis. Clin Nucl Med 2006;31:386-90. Disclosure of Interests: None declared